MODEL AND EXPERIMENT OF THE HYSTERIS CHARACTERISTICS ON MAGNETORHEOLOGICAL DAMPING LATHE TOOL - ZHANG YongLiang; GU Tao; PAN JianJian (Jixie qiangdu)
Cutting chatter is one of the major problems which constraints the high-performance and high-precision of the machining products. A damping lathe tool based on intelligent material — magnetorheological fluid was developed in order to effectively suppress cutting chatter by using excellent mechanical-electrical coupling characteristics of smart material. The investigations show that hysteresis nonlinearity is a characteristic of magnetorheological vibration damping device. So,an accurate mechanics model of damping lathe tool is essential to implement cutting chatter control effectively. A steady-state vibration testing platform was established in the paper. Through steady-state vibration experiment,force—displacement hysteresis curves have been explored under different excitation current and vibration frequency. Based on the theory of nonlinear hysteresis and combined with the data decomposition and parameter identification,the nonlinear elastic force、damping parameter、the hysteresis stiffness and hysteretic restoration force are calculated. It lays a theoretical foundation for chatter control with the damping lathe tool later.